River engage: Insights on plastic debris polluting the Aturukuku River in Uganda, the Ayung River in Indonesia, and the Connecticut River in the United States - Owens, Katharine A.; Kamil, Puspita Insan; Ochieng, Hannington (Frontiers in Environmental Science, 2023)
Introduction: Plastic waste in freshwater ecosystems is increasingly recognized as an economic, ecological, and environmental problem with potential health consequences. This article shares the results of a project to train local stakeholders to collect debris in their communities using scientific methods, then share the results with policymakers. Methods: Workshops were held in Uganda, Indonesia, and the United States in the spring of 2022. This article presents baseline data from collections on the Aturukuku River in Uganda, the Ayung River in Indonesia, and the Connecticut River in the United States as well as survey results measuring participant attitudes, behaviors, and their perceptions around plastic waste and policy. Surveying participants sheds light on the nuances of perception of the problem and policies to combat pollution at each locale. Results: We found deposited debris at each riverbank location: Aturukuku River, 0.45 pieces/m2 of which 89.4% was plastic; Ayung River, 7.62 pieces/m2 of which 91.1% was plastic, and the Connecticut River 0.29 pieces/m2 of which 63% was plastic. Environmental attitudes and behaviors were comparable among countries. Participants in all three countries expect plastic will be the most frequently found material. Discussion: In all cases, perceptions about the kind of debris in their communities corresponds well with collection results. Perceptions around policy solutions included a wide range of solutions, though countries differed in whether solutions addressed the source or the symptoms of the problem; solutions focused more on waste management in Uganda and Indonesia.